About electron energy increase in discharge with the non-sinusoidal field - Ostroushko, V. (Вопросы атомной науки и техники, 2013)
It is shown that the energy of electrons increases in the case of nonzero value of power spectral density at resonant frequencies irrespective of field strength jumps presence or absence. It is noted the inevitability of the collisional heating and its considerable contribution to the development of ionization.